Identification of key challenges associated with the implementation of renovation & modernization (r & m) projects in India using factor analysis - Bajpai, Purnima; K. Chandrashekhar Iyer, Prof.; Bansal, Shubham (International Journal of Engineering and Technology, 2018)
The Renovation & modernization (R&M) of coal fired thermal power plants deals with making the power plants units well equipped with the latest technology and systems with an aim of improving their overall performance in terms of output and availability as compared to the original design values, reduce the maintenance cost and enhanced efficiency. The aim of this study was to identify the key challenges associated with implementation of R & M Projects in India. An exploratory study of 42 variables was conducted through factor analysis using the data obtained through a questionnaire survey approach The results obtained 6 key challenges , namely Contractual risks, funding risks, planning risks, regulatory risks, market related risks and management risks which hamper the rate of implementation of R & M Projects in India.
Keywords: Renovation & Modernization (R & M); Factor Analysis; Challenges and Implementation.